2015
DOI: 10.1037/law0000024
|View full text |Cite
|
Sign up to set email alerts
|

Excusing murder? Conservative jurors’ acceptance of the gay-panic defense.

Abstract: We conducted a simulated trial study to investigate the effectiveness of a “gay-panic” provocation defense as a function of jurors’ political orientation. Mock jurors read about a murder case in which a male defendant claimed a victim provoked the killing by starting a fight, which either included or did not include the male victim making an unwanted sexual advance that triggered a state of panic in the defendant. Conservative jurors were significantly less punitive when the defendant claimed to have acted out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 39 publications
(60 reference statements)
6
42
2
Order By: Relevance
“…Not surprisingly, conservative political orientation predicted less support for penalty enhancement, which is in line with Cabeldue et al's (in press) reported pattern of political conservatism being linked with negative views of hate crime victims and laws (in general). These patterns also contribute to a building literature suggesting a general political identity is related to perceptions and decisions concerning laws and policies dealing with minority issues (e.g., gay panic defense, hate crime laws; Cabeldue et al, in press;Johnson & Byers, 2003;Salerno et al, 2015). Finally, this finding is supported by Johnson and Byers' (2003) findings that conservative individuals were less supportive of hate crime laws when sexual minorities were included as a protected group.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Not surprisingly, conservative political orientation predicted less support for penalty enhancement, which is in line with Cabeldue et al's (in press) reported pattern of political conservatism being linked with negative views of hate crime victims and laws (in general). These patterns also contribute to a building literature suggesting a general political identity is related to perceptions and decisions concerning laws and policies dealing with minority issues (e.g., gay panic defense, hate crime laws; Cabeldue et al, in press;Johnson & Byers, 2003;Salerno et al, 2015). Finally, this finding is supported by Johnson and Byers' (2003) findings that conservative individuals were less supportive of hate crime laws when sexual minorities were included as a protected group.…”
Section: Discussionsupporting
confidence: 63%
“…We define political identity in the present study as one's self-reported global or overall identity along a continuum ranging from conservative to liberal, a definition employed in literature concerning public perceptions of sexuality and legal policies (e.g., Markus-Newhall, Blake, & Baumann, 2002;Salerno et al, 2015). As evidenced by the legislative debate surrounding the HCPA of 2009 (HRC Foundation, 2013), political ideology likely plays a role in the support for hate crime laws.…”
Section: Predictors Of Penalty Enhancement Viewsmentioning
confidence: 99%
See 3 more Smart Citations